Sentiment Analysis and Marketing Mix in Twitter Conversations About Mixue - Arifiansyah, Rully (Ilomata International Journal of Management, 2024)
This study delves into the rapid growth and public reception of Mixue, a Chinese beverage and ice cream franchise, in post-pandemic Indonesia. Employing Twitter sentiment analysis through the lens of the 7P marketing mix framework (Product, Price, Promotion, Place, People, Process, Physical Evidence), the research evaluates consumer attitudes towards Mixue amidst its explosive expansion and recent Halal certification. Data was collected through Twitter API and Scrapy, encompassing 7087 Indonesian-language tweets related to Mixue between January and February 2023. Sentiment analysis revealed an overall positive reception towards Mixue, particularly regarding its products and affordability. However, concerns emerged surrounding limited flavor variety, perceived high prices, promotional saturation, and queuing difficulties. Implications of these findings highlight the importance of franchise businesses adapting to evolving consumer preferences in the post-pandemic market. Mixue could benefit from diversifying its menu, addressing queuing issues, and tailoring promotions to enhance the customer experience. Gaining insights into public sentiment allows Mixue and other franchises to refine their strategies and maintain long-term success in the ever-changing Indonesian market. This research serves as a valuable stepping stone for further exploration into consumer preferences for specific flavor variations, conducting price comparisons, evaluating promotional effectiveness, and optimizing outlet placement and customer service.Addressing these aspects can fuel Mixue's continued growth and strengthen its position within the thriving Indonesian food and beverage landscape.